Pengaruh Fasilitas Kerja dan Pelatihan terhadap Kinerja Karyawan di Koperasi Purna Karya Pertamina Medan - Victor; Melinda Sinaga, Triana; Manalu, Tamara (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2024)
The aim of this scientific work is to determine the effect of work facilities and training on employee performance at the Medan Purna Karya Cooperative. Furthermore, this scientific work uses a quantitative descriptive research methodology, namely a statistical method used to analyze data by describing or illustrating the data that has been collected. Furthermore, the data sources used are primary data and secondary data. In this research or scientific work, all 46 employees working at the Medan Purna Karya Cooperative were used as respondents. The results of further data analysis are that work facilities have a t value > t table (5.261 > 2.016) with a significant value of 0.000 < 0.050, and the job training variable has a t value > t table t table (2.220 > 2.016) with a significant value of 0.032 < 0.050. The research results also state that there is an influence between facilities and job training on employee performance. This is proven by the value of Fcount > Ftable (13.899 > 2.816) and a significant value of 0.000 < 0.05.